2015
DOI: 10.1016/j.eurpsy.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Neuropsychiatry: White Matter Abnormalities in Children and Adolescents with Schizophrenia, Bipolar Affective Disorder, and Obsessive-Compulsive Disorder

Abstract: White matter abnormalities in early-onset schizophrenia and bipolar affective disorder are more global in nature, whereas children and adolescents with obsessive-compulsive disorder do not show widespread differences in FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…In general, demyelinating diseases are classified as neurological diseases but not psychiatric diseases. However, cognitive dysfunction is observed in patients experiencing demyelination (Malkki 2015), and white matter abnormalities are found in many SCZ patients (White et al 2015). In our previous study using demyelinating PLP 4e/À mice, we observed cognitive dysfunction prior to the onset of demyelination (Tanaka et al 2009).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In general, demyelinating diseases are classified as neurological diseases but not psychiatric diseases. However, cognitive dysfunction is observed in patients experiencing demyelination (Malkki 2015), and white matter abnormalities are found in many SCZ patients (White et al 2015). In our previous study using demyelinating PLP 4e/À mice, we observed cognitive dysfunction prior to the onset of demyelination (Tanaka et al 2009).…”
Section: Discussionmentioning
confidence: 85%
“…An imbalance of the inhibitory-excitatory activities within the neural network in the CNS can cause psychiatric diseases (Cui et al 2016). White matter abnormalities can also play roles in psychiatric diseases, especially during the juvenile and adolescent periods (White et al 2015). Several studies have demonstrated that a decrease in oligodendrocyte number and altered expression of myelin/oligodendrocyte-related genes in schizophrenia (SCZ) patients could affect white matter morphology and neuronal connectivity, which are characteristic features of SCZ (Martins-de-Souza et al 2009).…”
mentioning
confidence: 99%
“…In summary, results from the current study suggest that inferences regarding the spatial distribution of SSA across multiple individuals following various z-transform methodologies are not statistically valid unless an independent third group is utilized for the initial z-transform. Although it has been repeatedly demonstrated that the LOO, IDS, EZ-MAP and DisCo-Z methods eliminate group-wise bias when SSA are summed across individuals (Bouix et al 2013; Kim et al 2013; Mayer et al 2014; Mayer et al 2017), recent attempts to quantify the number of individuals who exhibit SSA within the same voxel/region (Bouix et al 2013; Hayes et al 2015; Meier et al 2016; Miller et al 2016; Miller et al 2016; Solmaz et al 2017; Taber et al 2015; White et al 2013; White et al 2015) or compute weighted statistics based on the proportion of individuals with extreme values (Ware et al 2017) may be statistically flawed depending on the transform method utilized. Specifically, any SSA z-transform (e.g., LOO and DisCo-Z methods) that utilizes the first two statistical moments (mean and standard deviation) for both the transform itself as well as for subsequent comparison purposes will produce a bias in the spatial location of extrema.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a growing number of investigators have examined the spatial overlap of extrema across subjects within individual voxels or regions of interest (ROI) following various z-transform methods (Bouix et al 2013; Hayes et al 2015; Meier et al 2016; Miller et al 2016; Miller et al 2016; Solmaz et al 2017; Taber et al 2015; White et al 2013; White et al 2015). Specifically, these studies have quantified the number of individuals who exhibit SSA within the same voxel or region rather than collectively examining the total number of SSA across all voxels/regions.…”
Section: Introductionmentioning
confidence: 99%
“…White et al (2009) [ 65 ] discovered white matter “potholes”, which are FA hypo-intensities that are spatially unique to each subject. While pothole locations often do not overlap between subjects, the occurrence of potholes tends to be higher in subject groups than in controls [ 65 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%